2015
DOI: 10.1371/journal.pone.0135811
|View full text |Cite
|
Sign up to set email alerts
|

Bispyridinium Compounds Inhibit Both Muscle and Neuronal Nicotinic Acetylcholine Receptors in Human Cell Lines

Abstract: Standard treatment of poisoning by organophosphorus anticholinesterases uses atropine to reduce the muscarinic effects of acetylcholine accumulation and oximes to reactivate acetylcholinesterase (the effectiveness of which depends on the specific anticholinesterase), but does not directly address the nicotinic effects of poisoning. Bispyridinium molecules which act as noncompetitive antagonists at nicotinic acetylcholine receptors have been identified as promising compounds and one has been shown to improve su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 33 publications
1
25
0
2
Order By: Relevance
“…The following compounds were prepared according to published methods:p ropane-1,3-diyl bis(trifluoromethanesulfonate) (21), [44,45] 2-tert-butylpyridine (17), [27] 2-(pyridin-3-yl)propan-2-ol (9), [33] rac-nicotine (rac-26), [28] 1-(tert-butyl)-1H-imidazole (41) [29] and the 4-tertbutyl-substituted pyridine derivatives 4-(tert-butyl)-3-methylpyridine (33), 4-(tert-butyl)-3-methoxypyridine (31), 4-(tert-butyl)-3chloropyridine (28), 3-bromo-4-(tert-butyl)pyridine (29), 4-(tert-butyl)pyridine-3-carbonitrile (30), ethyl 4-(tert-butyl)pyridine-3-carboxylate (36), 4-(tert-butyl)-3-fluoropyridin-1-ium chloride (27), 4-(tertbutyl)-3-phenylpyridine (34), 4-(tert-butyl)-N,N-dimethylpyridine-3carboxamide (32), and 4-(tert-butyl)-3-ethynylpyridine (35). [30] Generalprocedures Synthesis of symmetric bispyridinium compounds by N-alkylation with 21 (GP1): 21 (1.0 equiv) was carefully added to asolution of the corresponding pyridine derivative (2.5 equiv) in CH 2 Cl 2 (0.8 mL mmol À1 )o rt ot he neat pyridine derivative (2.5 equiv) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following compounds were prepared according to published methods:p ropane-1,3-diyl bis(trifluoromethanesulfonate) (21), [44,45] 2-tert-butylpyridine (17), [27] 2-(pyridin-3-yl)propan-2-ol (9), [33] rac-nicotine (rac-26), [28] 1-(tert-butyl)-1H-imidazole (41) [29] and the 4-tertbutyl-substituted pyridine derivatives 4-(tert-butyl)-3-methylpyridine (33), 4-(tert-butyl)-3-methoxypyridine (31), 4-(tert-butyl)-3chloropyridine (28), 3-bromo-4-(tert-butyl)pyridine (29), 4-(tert-butyl)pyridine-3-carbonitrile (30), ethyl 4-(tert-butyl)pyridine-3-carboxylate (36), 4-(tert-butyl)-3-fluoropyridin-1-ium chloride (27), 4-(tertbutyl)-3-phenylpyridine (34), 4-(tert-butyl)-N,N-dimethylpyridine-3carboxamide (32), and 4-(tert-butyl)-3-ethynylpyridine (35). [30] Generalprocedures Synthesis of symmetric bispyridinium compounds by N-alkylation with 21 (GP1): 21 (1.0 equiv) was carefully added to asolution of the corresponding pyridine derivative (2.5 equiv) in CH 2 Cl 2 (0.8 mL mmol À1 )o rt ot he neat pyridine derivative (2.5 equiv) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…This problem could, however,b eovercome using the far more reactivep ropane-1,3-diyl bis(trifluormethanesulfonate) (21). This problem could, however,b eovercome using the far more reactivep ropane-1,3-diyl bis(trifluormethanesulfonate) (21).…”
Section: Preparation Of the Target Compoundsmentioning
confidence: 99%
“…Among them, the direct block exerted by certain bispyridinium oximes on nAChR ion channels, which correlates with recovery of neuromuscular function in soman‐poisoned nerve–muscle preparations, was demonstrated . Based on this finding, bispyridinium non‐oximes were developed to optimize this aspect of bispyridinium action to improve recovery of neuromuscular function by a presumed non‐competitive mechanism of action . It has also been suggested that these bispyridinium non‐oximes possibly interact with nAChR subtypes as positive allosteric modulators .…”
Section: Discussionmentioning
confidence: 99%
“…A atividade do receptor pode ser inibida por mecanismos não-competitivo e alostéricos (o ligante não compete com agonistas e se liga a outro sítio, que não o ativo) bem como por mecanismo competitivo (em que há competição no sítio ativo com agonistas). A inibição não competitiva e alostérica do RAChn foi observada para anestésicos locais, como a procaína e a lidocaína (Pagan et al, 2007;Rhee et al, 2015), assim como para agentes bloqueadores neuromusculares (incluindo sais de amônio quaternários, como o QX-222) (Gentry & Lukas, 2001;Heiny et al, 2010;Ring et al, 2015), que serão apresentados a seguir.…”
Section: Efeitos Do Par Iônico Sobre a Lipofilicidadeunclassified
“…A interação entre agentes bloqueadores neuromusculares e os receptores nicotínicos, localizados na junção neuromuscular esquelética, pode ser denominada bloqueio da transmissão neuromuscular. O bloqueio da transmissão neuromuscular pode ocorrer por interrupção dos impulsos nervosos na junção neuromuscular, causando paralisia ou relaxamento dos músculos esqueléticos (Bowman, 2006;Ring et al, 2015). Estudos envolvendo a relação entre a estrutura e a atividade de agentes bloqueadores neuromusculares sugerem que tanto a presença de grupos com carga positiva bem como a lipofilicidade são características importantes que contribuem para a(s) interação (ões) com o RAChn (Siqueira, 2001;Bowman, 2006;Pagan et al, 2007;Ring et al, 2015).…”
Section: Efeitos Do Par Iônico Sobre a Lipofilicidadeunclassified